Evaluation foot self care in diabetic patients. Retrospective Analysis (2008-2013) - Navarro-Flores, Emmanuel; Gijón-Noguerón, Gabriel; Cervera-Marín, José Antonio; Labajos-Manzanares, María Teresa (Revista Internacional de Ciencias Podológicas, 2013)
Purpose: The purpose of this study is to analyze other studies and research on foot self care and self-examination in patients with diabetes, taken from different sources of the scientific literature. Methods: The authors carried out a systematic review of published studies (including clinical trials, meta-analysis and Cochrane reviews), about the evaluation of health habits and health education concerning foot care in patients with diabetes. The authors researched articles using the terms “diabetic foot self-care, diabetic foot self-management, diabetes self-care and diabetes selfmanagement” in the Medline, Web of Science, Cochrane Database, CINAHL, Scopus and EMBASE databases. Only 33 of the studies found here and published between January 1990 and May 2012 fulfilled the requirements, as they dealt with medical procedures to reduce the complications in feet caused by diabetes. Results: Of a total of 479 studies identified, the authors previously selected 50, of which 34 were from Pubmed, 12 from Web of Knowledge and four from Cochrane. In the end, they only chose 33 in order to develop this research, of which three were on metaanalysis, four were systematic reviews, six were randomized clinical trials, three were observational studies and 17 were review articles. Conclusions: All the analyzed studies present strategies directed towards a change in behavior. These strategies are effective regarding the metabolic control of the illness and the reduction of amputations. But it is necessary to validate a reliable tool to determine the development of healthy habits and to guarantee their continued practice, given that most studies present a lack of methodology regarding sample selection and time of study.
Keywords: foot care; self care; self management; diabetic foot.